Marginal deterrence in the enforcement of law: Evidence from distributed denial of service attack - HUI, Kai-Lung (Institutional Knowledge at Singapore Management University, 2013)
By studying a panel dataset of distributed denial of service attack across 240 countriesover 5 years, we find that enforcing the Convention on Cybercrime had increasedthe intensity of attack by 43 to 52 percent. It did not significantly reducethe chance for a country to be selected for the attack. We conducted a batteryof identification and falsification tests to show that such increased attack intensityarose because of failure in marginal deterrence, instead of other theories such asbrutalization, stigmatization, or defiance, or general forms of endogeneity. We showthat raising the standard of proof of conviction is one way to facilitate marginaldeterrence, but it has the undesirable effect of raising the offense rate. We discussother possible solutions.